A mathematical model for Lassa fever transmission dynamics in a seasonal environment with a view to the 2017–20 epidemic in Nigeria. (August 2021) - Ibrahim, Mahmoud A.; Dénes, Attila
Abstract: In this paper, we formulate and study a compartmental model for Lassa fever transmission dynamics considering human-to-human, rodent-to-human transmission and the vertical transmission of the virus in rodents. To incorporate the impact of periodicity of weather on the spread of Lassa, we introduce a non-autonomous model with time-dependent parameters for rodent birth rate and carrying capacity of the environment with respect to rodents. We introduce the basic reproduction number and show that it can be used as a threshold parameter concerning the global dynamics. It also shown that the disease-free periodic solution is globally asymptotically stable in the case of R 0 < 1 and if R 0 > 1, then the disease persists. We show numerical studies for the Lassa fever in Nigeria and give examples to describe what kind of parameter changes might trigger the periodic recurrence of Lassa fever.